Phylogenetic relationships and biogeography of Asia Callicarpa (Lamiaceae), with consideration of a long-distance dispersal across the Pacific Ocean —insights into divergence modes of pantropical flora - Cai, Huimin; Liu, Xing; Wang, Wenqiao; Ma, Zhonghui; Li, Bo; Bramley, Gemma L. C.; Zhang, Dianxiang (Frontiers in Plant Science, 2023)
There are about 140 species of Callicarpa, with more species richness in tropical to subtropical Asia and the New World. The genus might provide an insight into the amphi-Pacific disjunction pattern of tropical and subtropical vegetation. This study has greatly improved the phylogenetic underpinning for Callicarpa, derived from more inclusive taxonomic samplings, and employing data on both two-nuclear and eight-chloroplast regions. Our phylogenetic results showed that Callicarpa is monophyletic with respect to the groups considered, and eight well-supported primary clades were discerned in the combined analyses. To address time, patterns, and processes of diversification in Callicarpa, we conducted divergence time and biogeographic analyses, and inferred shifts in the distribution areas across the phylogenetic clades. Our estimates indicated that the crown group of Callicarpa originates around the Late-Eocene (ca. 36.23 Ma) and diversification within most clades is concentrated in the Miocene and continued to the Pleistocene. In addition, our biogeographic analyses suggested that the probable ancestor of the Callicarpa crown clade originated in East Asia and Southeast Asia. Multiple dispersal and vicariance events contributed to the current distribution of the taxa. Furthermore, simultaneously, this genus expanded eastward out of East and Southeast Asia to the New World by long-distance dispersal, which inspired us to better understand the amphi-Pacific disjunct distribution.